Integration of a light mobility urban scale hydrogen refuelling station for cycling purposes in the transportation market. (27th January 2021) - Apostolou, Dimitrios; Casero, Pedro; Gil, Vanesa; Xydis, George
Abstract: Road transportation consists of a significant contributor to total greenhouse gas emissions in developed countries. New alternative technologies in transportation such as electric vehicles aim to reduce substantially vehicle emissions, particularly in urban areas. Incentives of using two-wheel electric vehicles such as bicycles in big cities centres are promoted by local governments, and in fact, some countries are already trying to adopt this transition. An interesting case consists of the use of hydrogen fuel cells in such vehicles to increase their driving range under short refuelling times. To this end, this paper investigated the social and financial prospects of hydrogen infrastructure for city-oriented fuel cell electric vehicles such as bicycles. The results of the research indicated that a light mobility urban hydrogen refuelling station able to provide refuelling processes at pressures of 30 bar with a hydrogen fuel cost of 34.7 €/kgH2 is more favourable compared to larger stations. Highlights: Operation and multiple-pressure refuelling processes of a hydrogen-fuelled bicycle. Estimation of the autonomy of a fuel cell electric bicycle. Hydrogen price calculated tο range between 34.7 and 36.9 €/kgH2 . Hydrogen fuel cost per km calculated to approximately 0.019 €/km.